Badge of Rebellion The Mariinsky Ballet in London - Craine, Debra 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
The Mariinsky Ballet in London. Valery Gergiev insists that there is a new phase at the Mariinsky.